(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2017)
The basic problem facing public institutions and banks, especially in how to achieve the economic development process aimed at a kind of balance between economic and environmental aspect, as well as ambiguity clear mechanism conducted by the knowledge and inventory and determine the costs incurred by the banks to participate in maintaining environmental, and thus banks began take the kind of attention to the environmental aspect of development when economic policy-making way that achieves the optimal use of natural and environmental resources, and to achieve that banks have sought to use technology as a means of mitigating the negative effects of development processes on Environment, and it pursued the Iraqi commercial banks, banks and other institutions approach. As taking a growing interest in the environmental side by spreading environmental culture among all employees it began to achieve sustainable excellence for others and work to create and innovate services and creative processes contribute to the creation of new markets and to reduce the associated social environment to provide product problems. The study measured the readiness of the environmental dimension through the work of its own identification and purpose is to stand over the possibility of applying and know whether Iraqi banks have sufficient knowledge of the environmental impact of its operations and banking activities. The study was conducted according to the statistical program (spss) as well as measuring the validity and stability of the questionnaire by testing the degree of credibility by Alpha Crombach to test and measure the degree of credibility (reliability) in the responses from the questionnaire questions. This study reached many conclusions, And to be part of the development processes and achieve sustainability for the coming years. One of the most important recommendations of this study is the need to contribute to the preparation of environmental pollution costs reports at the national level, Resulting from the different activities of the units, and demand associations, scientific bodies and economic units of the need to disclose data on environmental activities to meet the new societal goals and needs him.